Influence Of Branding to Brand Awareness in Dental Hospital Of Hang Tuah University - Ghita Hadi Holanda (Denta Journal Kedokteran Gigi, 2017)
Background: The company is able to be the basis of the formation of customer loyalty and fanaticism of the product or service through a strong brand. Having a strong brand is a vital aspect for any company, because the advantage gained diverse. Based on the data in 2014 and 2015, it showed the decreased number of patients at the Dental Hospital of Hang Tuah University (UHT Dental Hospital) from 2014 to 2015 amounted to 949 people (8%), as well as the number of patients in the Polyclinic of Medical Specialists of UHT Dental, were 14,6% (348 patients) from ideal capacity (2384 patients). Purpose: The aim of this study is to find out the influence of branding to brand awareness in dental hospital of Hang Tuah University. Materials and Methods: This study was an observational study that used 200 respondences from the patients population of UHT Dental Hospital. The study was conducted at UHT Dental Hospital from March-April 2016. Result: The results showed that the characteristics of patients who seek treatment at the UHT Dental Hospital were majority adults in productive age (25-35 years old), at middle to lower-end of socio-economic class, and had the education level of SLTA grade. Most of respondents had bad perception for the brand attributes of UHT Dental Hospital. Most of them had low brand awareness. The majority of respondents rated the branding of UHT Dental Hospital were bad. Conclusion: There was a tendency if the branding were good, the brand awareness was getting better.